O DESAFIO DA GESTÃO SOCIALMENTE RESPONSÁVEL E AS INTERAÇÕES DOS STAKEHOLDERS: UM ESTUDO MULTICASOS - Alves, Edna Ribeiro (2011)
The relationship company & stakeholders is presented within a complex network. This statement not only argues with the traditional linear theory of stakeholders, as it indicates the establishment of conflicts in this audience interaction. According to the level of influence of variables such as power, legitimacy and urgency, variables that compose the model adopted for this study‟s research, the actions of corporate social responsibility of organizations seem to be impacted by that interaction. This research aims to present a study on the interrelationship between corporate managers and stakeholders to the practices of Corporate Social Responsibility (CSR). For this purpose, a case study was conducted in which managers were interviewed through a semi-structured questionnaire, aiming at identifying how these interactions occur and how they impact on the actions of CSR. As a theoretical basis, the state of art of the concepts involved in the subject is presented, including: stakeholder; social responsibility/corporate social responsibility, ethics/morality and transparency; the ISO 26000 and its multistakeholder relationship character and Sustainability.